IMPROVING STUDENTS’ WRITING SKILL THROUGH INSTAGRAM STORIES - Rafika Purba; Ersika Puspita Dani; Khairunnisa .; Kicky Maulana (Jurnal Education and Development, 2021)
This research deals with the Writing Skill. The problems of this research are to know the improving students’ writing skill of the eighth grade students of Junior high school in MTsN 1 Deli Serdang in the academic year of 2021/2022. The objective of this research is to find out the use of the Instagram Stories can improve students‟ writing skills especially in descriptive text. The method will use pre-experimental method. The population of this research is the eighth-grade students of Junior high school in MTsN 1 Deli Serdang in the academic year of 2021/2022. The sample consisted 25 students participants. The instrument will use the test, which was distributed in pre-test and post-test sessions.